Extensive Polygonal Fracture Network in Siccar Point group Strata: Fracture Mechanisms and Implications for Fluid Circulation in Gale Crater, Mars. Issue 10 (28th October 2019) - Kronyak, R. E.; Kah, L. C.; Miklusicak, N. B.; Edgett, K. S.; Sun, V. Z.; Bryk, A. B.; Williams, R. M. E.
Abstract: Rock fractures are indicators of stress release within geologic systems, and fracture morphologies can commonly be used to infer formation conditions. Polygonal fractures are common in isotropic, contractional stress regimes such as in rocks exposed at the surface of a planet undergoing thermal cycling or in sedimentary substrates undergoing repeated wetting and drying. Such polygonal fracture systems, on centimeter to decameter scales, have been widely documented on Mars. Utilizing a combination of orbital‐ and ground‐based images, we report a laterally extensive polygonal fracture network that occurs within siliciclastic rocks of the lowermost Siccar Point group, Gale crater, Mars. The Siccar Point group is exposed over approximately 20 km 2 in northwest Gale crater, where it unconformably overlies eroded strata of Mount Sharp (Aeolis Mons) and reflects likely aeolian deposition along the lower flanks of Mount Sharp. Images reveal an extensive network of erosionally resistant polygons, approximately 7.5 m across, that exhibit interior angles (i.e., fracture intersections) with modes at 90° and 120°. Polygon morphology indicates that fractures formed during multiple cycles of expansion and contraction, which is attributed to desiccation and subsequent recharge of near‐surface groundwater. The erosional resistance of preserved fractures is inferred to reflect postfracture diagenetic fluid flow along the sub–Siccar Point group unconformity and cementation. Evidence for multiple fluid events in the relatively young strata of the Siccar Point group requires a protracted history of fluid stability in Gale crater. Plain Language Summary: Deciphering the processes that affect sedimentary rocks after their deposition is critical to understanding the geologic history of a basin. Fractures occur when applied forces exceed the strength of the host material, and we can infer the process by which fracturing occurred by assessing the morphology of fractures. In this study, we analyze a network of polygonal fractures within rocks of the Siccar Point group, a relatively young geologic unit that is exposed over ~20 km 2 of Gale crater, the field site of the Curiosity rover. Polygons formed by these fractures are similarly sized and intersect at angles that show dominant modes at 90° and 120°. These observations suggest that fractures formed under conditions of uniform stress and likely result from contractional processes such as climate‐driven wet‐dry cycles. The cementation of fractures by later fluids then imparted erosional resistance that permits these features to be recognized from orbit. The presence of an extensive, fluid‐driven fracture system within aeolian strata highlights the potential complexity of martian climate signals. Key Points: Siccar Point group strata record extensive fracturing and fluid flow, resulting in a regional network of erosionally resistant polygons Polygons reflect single to multiple cycles of sediment contraction associated with evaporation and recharge of near surface fluids The presence of fluid‐related fractures within a predominantly dry aeolian system highlights potential variability in martian climate